KEPUTUSAN PETANI SAWIT DALAM MENGKONVERSI LAHAN KELAPA SAWIT MENJADI LAHAN PADI SAWAH DI KECAMATAN BATANG ASAM KABUPATEN TANJUNG JABUNG BARAT - Ompusunggu, Krielson; Lubis, Arsyad; Kurniasih, Siti (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
Farmers in Batang Asam Subdistrict have two choices, namely to join the Government's Revitalization program by converting their productive age oil palm plantations into paddy fields or exchanging land with other farmers or selling their land and then buying land in different places. The purpose of this study is to determine the factors that influence the decision of farmers to convert their oil palm plantation land into paddy fields. The approach used in this research is a quantitative approach. Primary data is collected through observation, interviews, and special discussions with selected speakers. The sampling method in this study was done by Simple Random Sampling Technique. The analysis tool used is the Godnes Of Fit Test with the same expected frequency. The results of this study indicate that the decision of farmers to convert their oil palm plantation land into lowland rice fields is influenced by psychological factors, the price factor of paddy fields, and the factor of two branches of farming.